Hubungan Tingkat Pengetahuan Dan Dukungan Keluarga Terhadap Kepatuhan Diet Pada Pasien Hipertensi Rawat Jalan Di RSUD Dr. R. Koesma Tuban - Diny Mayang Prastika; Choirul Anna Nur Afifah (Lembaga Pengembangan Kinerja Dosen, 2024)
Hypertension as silent disease or silent killer i.e. escalation of systolic blood pressure is higher or equal to 140mmHg, and escalation of diastolic pressure is higher or equal to 90 mmHg. High prevalence of hypertension need to get the right treatment. The situation analyst at Dr. R. Koesma Tuban Hospital, obtained two from five patient have not complied with instructions by local doctor. This Study intend : (1) acknowledge relationship level of knowledge toward diet obedience in outpatient hypertension at Dr. R. Koesma Tuban Hospital, (2) acknowledge relationship family support toward diet obedience in outpatient hypertension at Dr. R. Koesma Tuban Hospital. This Study uses correlation, using a cross sectional approach. This study held in Dr. R. Koesma Tuban Hospital and several respondent houses. Sample of this study come to 22 respondent using total sampling technique. Data retrieval by test and questionnaires. Then, the data were analyzed by frequency distribution and Chi-square Test. Based on the results of this research were obtained respondents have good knowledge (27,3%) Family support with a good values (50%). Result of bivarate analysis knowledge p value>0,05, so then there is uncorelattion between knowledge with diet obedience. Whereas, result of family support p value <0,05, so then there is a relationship between family support with diet obedience. Conclusion from the data show, that the variable level of knowledge has no relationship diet obedience in outpatients at Dr. R. Koesma Tuban, while family support be found relationship, toward diet obedience outpatient at Dr. R. Koesma Tuban Hospital.